Model Suggestion for the Investigation of the Textbooks to Be Used In Teaching Turkish as a Foreign Language (International Journal of Scientific Research and Management (IJSRM), 2020)
Textbooks are considered the most important course materials from past to present. Qualified and functional textbooks are required to achieve the desired objectives of education. Therefore, the processes of examining the textbooks to be used in teaching Turkish as a foreign language and carrying out scientific research on this subject is modelled in this article. A qualitative research method was used in this article. Both quantitative and qualitative data might be used in the studies carried out to examine the textbooks used in teaching Turkish as a foreign language. Therefore, the mixed methods research can be regarded as a suitable research design for examining textbooks. For the quantitative data, a 5-point Likert-type scale can be applied to instructors who use the textbooks, while a Rubrics can be applied to students. Also, the qualitative data obtained from researcher’s field notes, observations, interviews with the participants (instructors, students, and the experts of book design and printing), the questionnaires to be applied to them, and the analysis of the textbooks subject to research, as well as, the quantitative data obtained from checklists and semantic scales can be evaluated by following a holistic approach.